Necrotizing Periodontal Diseases II: Clinical Features - Maita Véliz, Luis V. (2016)
This article presents a review of the most important aspects from necrotizing periodontal disease, specia-lly about clinical features, diagnostics, etiology, evolution, prognose and treatment.